SYSTEMATIC REVIEW OF ADAPTIVE TEACHER COMPETENCE IN DIGITAL SKILLS FOR PRIMARY EDUCATION - Mochamad Guntur; Nur Indah Septia Ningsih; Indah Puspitaningsih; Amanda Maharani; Naufal Fida Sulaeman (Program Studi PGSD Universitas Flores, 2025)
This article represents a systematic literature review aimed at identifying the essential components to be considered during the development and design of adaptive teacher competence in digital skill accessibility. The methodology followed a rigorous and systematic approach, involving a thorough search for relevant texts pertaining to the subject of study, followed by careful selection, evaluation, and analysis. The research findings reveal that a considerable proportion of primary school teachers possess a moderate to high level of adaptive teacher competence in digital skills accessibility. These teachers demonstrate the ability to adapt instructional practices and effectively incorporate technology into their teaching processes. The findings also suggest that successful implementation of digital tools in education requires not only technical skills but also the ability to critically evaluate and integrate digital resources to enhance student learning outcomes. As digital transformation in education continues to evolve, it is crucial for educators to stay updated with emerging technologies and pedagogical strategies. Therefore, the study emphasizes the need for ongoing training programs and policy support to strengthen teachers' digital readiness and foster adaptive teaching practices across diverse educational settings.